2009
DOI: 10.1111/j.1749-6632.2009.04687.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1β–Induced Extracellular Matrix Degradation and Glycosaminoglycan Release Is Inhibited by Curcumin in an Explant Model of Cartilage Inflammation

Abstract: Osteoarthritis (OA) is a degenerative and inflammatory disease of synovial joints that is characterized by the loss of articular cartilage, for which there is increasing interest in natural remedies. Curcumin (diferuloylmethane) is the main polyphenol in the spice turmeric, derived from rhizomes of the plant Curcuma longa. Curcumin has potent chemopreventive properties and has been shown to inhibit nuclear factor kappaB-mediated inflammatory signaling in many cell types, including chondrocytes. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 29 publications
2
58
0
Order By: Relevance
“…Treatment of OA with novel agents that can simultaneously target multiple cellular signaling pathways in chondrocytes will benefit from effectively downregulating inflammation without adverse systemic effects. We and others have shown that phytochemicals such as curcumin and resveratrol target the catabolic pathways mediated by the NF-jB signal transduction pathway in cartilage and might be used as clinically safe nutritional factors for the treatment of OA [13,15,26,34,36,47,50,54]. We have also shown that resveratrol and/or curcumin stimulate Sox-9 expression and inhibit the IL-1b-induced decreased Sox-9 expression that is necessary for the expression of cartilage matrix genes [15].…”
Section: Introductionmentioning
confidence: 89%
“…Treatment of OA with novel agents that can simultaneously target multiple cellular signaling pathways in chondrocytes will benefit from effectively downregulating inflammation without adverse systemic effects. We and others have shown that phytochemicals such as curcumin and resveratrol target the catabolic pathways mediated by the NF-jB signal transduction pathway in cartilage and might be used as clinically safe nutritional factors for the treatment of OA [13,15,26,34,36,47,50,54]. We have also shown that resveratrol and/or curcumin stimulate Sox-9 expression and inhibit the IL-1b-induced decreased Sox-9 expression that is necessary for the expression of cartilage matrix genes [15].…”
Section: Introductionmentioning
confidence: 89%
“…21 In vitro studies have also shown that curcuminoids inhibit IL-1b-induced glycosaminoglycan (GAG) release from animal and human OA cartilage explants. 22,23 Randomized clinical trials (RCTs) in animals have suggested that Curcuma extracts (comprised of mixtures of Indian and Javanese turmeric with essential oils) may have beneficial effects in treatment of OA 24 and results of a recent large observational study including 820 adults with painful OA showed evidence of benefits with curcuminoids in real-life clinical practice. 25 Several clinical trials investigating the effect of curcuminoids in OA have also been published.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, race records showed that less than 80% of the 2-year-old racehorses in training completed their training and went on to race [1]. Although the causes of lameness are varied, increased attention has been focused on the role of inflammatory mediators in this process [4][5][6]. Inflammation is associated with the production of proinflammatory cytokines, which are small hormone-like proteins produced in response to external stimuli.…”
Section: Introductionmentioning
confidence: 99%